Tawhid al 'uluhiyya, secularism, and political Islam - Eddebo, Johan (The journal of religion & society, 2014)
In this paper, a particular aspect of the Islamic notion of tawhid is described and explored with regard to its consequences for Islam's relationship to secular society. It is argued that strains of Islam informed by the widespread, orthodox interpretation of this tawhid al 'uluhiyya, or "the oneness of creation's worship of God," cannot be coherently harmonized with the notion of a secular, political order wherein religion and the public sphere are strictly separated. On this basis, it is then argued that inclusion of non-secular political Islam within the framework of liberal democracy is likely a preferable development in the interests of minimizing future international and domestic conflict, and supporting autonomous popular rule in Islamic states.